Sol-Gel Coatings Doped with Encapsulated Silver Nanoparticles: Inhibition of Biocorrosion on 2024-T3 Aluminum Alloy Promoted by Pseudomonas Aeruginosa - Paez-Collio, M; Paez-Collio, M; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M; Gonzalez-Sanchez, E; Gonzalez-Sanchez, E (Elsevier Editora Ltda, 2019)
Silanol type hybrid polymers modified with silver nanoparticles encapsulated with SiO2 for biocorrosion protection of 2024-T3 aluminum alloy were studied through electrochemical characterization and surface analysis techniques. Two different encapsulated silver nanoparticles were synthesized using tetraethoxysilane as a core shell. The hybrid polymer was prepared by the sol-gel technique by mixing tetraethoxysilane and triethyl(octyl)silane in 1-propanol, followed by the incorporation of silver nanoparticles or encapsulated silver nanoparticles. Relatively uniform coatings were observed by a scanning electron microscopy analysis. Transmission electron microscopy and dynamic light scattering results indicated that the diameter of the silver nanoparticles was around 20 nm, whereas the encapsulated silver nanoparticles presented diameters between 24 and 30 nm. The viability results showed that polymers modified with encapsulated nanoparticles exhibit higher antibacterial properties than the polymer modified with free silver nanoparticles. This fact may be associated with a higher hydrophobicity of the coatings modified with silver encapsulated nanoparticles. Additionally, impedance measurements revealed a protective effect of all synthesized coatings for 2024-T3 aluminum alloy in chloride media inoculated with Pseudomonas aeruginosa. © 2019 Brazilian Metallurgical, Materials and Mining Association. Published by Elsevier Editora Ltd.
Keywords: Hybrid polymers; Silver nanoparticles; SiO2 nanocapsules; Biocorrosion; Pseudomonas aeruginosa